Dynamic linkages among Saudi market sectors indices - Farouq Altahtamouni; Hajar Masfer; Shikhah Alyousef (Economies, 2022)
This study aims to test the causal relationship between Saudi stock market index (TASI) and sectoral indices throughout the period from 2016-2020. The study data were extracted through the main index of the Saudi market and the indices of the available data of 19 sectors out of 21 sectors. The unit root test was used along with the Granger causality test, in addition to multiple regression tests in order to analyze the study hypotheses. The study shows that all index series were stationary at the zero level I (0), and the results also show that there were bidirectional and unidirectional causal relationships between TASI and sectoral indices, and that TASI effectively mirrors all the changes that occur in the Saudi stock market.
Keywords: 330; granger causality; sectoral indices; TASI; unit root